III Seminário de Ensino, Pesquisa e Extensão do IFRO – Campus Ji-Paraná - IFRO – Campus Ji-Paraná, ANAIS DO III SEPEX - (South American Journal of Basic Education, Technical and Technological, 2018)
III Seminário de Ensino, Pesquisa e Extensão do IFRO – Campus Ji-Paraná